Reading Comprehension Problem and Solution in Online Classroom - Mudia, Suhufam; Devanti, Yeni Mardiyana; Nurkamilah, Nurkamilah (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
The research focus on finding the problem and solution of reading comprehension in online learning class at ninth grade in 2022/2023 Academic Year. The research problems are focused on; 1. How do students learn reading comprehension in online learning class? 2. What kind of problems faced by students in studying reading comprehension in online learning class?, 3. What strategies can be used by students to solve the problems in online learning class?. To find the answer of the problem above descriptive qualitative research was conducted. The results of this research were in the form of words and sentences. It was found that some strategies were used by students as scan reading to save time and reduced eye strain due to gadget light, form a small group study with students who are near home to join reading class together and discuss about the material. if students found it was hard to read by smartphones or laptop some students print out the assignment given by teacher. Therefore, students could read easily, and underline the important information directly. Different from previous studies, this research, in addition to finding problems, also offers useful solutions for online reading learning.